If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.7(x + 9) = 15 Reorder the terms: 0.7(9 + x) = 15 (9 * 0.7 + x * 0.7) = 15 (6.3 + 0.7x) = 15 Solving 6.3 + 0.7x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.3' to each side of the equation. 6.3 + -6.3 + 0.7x = 15 + -6.3 Combine like terms: 6.3 + -6.3 = 0.0 0.0 + 0.7x = 15 + -6.3 0.7x = 15 + -6.3 Combine like terms: 15 + -6.3 = 8.7 0.7x = 8.7 Divide each side by '0.7'. x = 12.42857143 Simplifying x = 12.42857143
| 20x+5=19x+11 | | -2x+13=.5x-20 | | 26d=520 | | 231+10x=18y+5 | | 6x^2+10=2x^2+30 | | m+-255=2 | | (7y+8)-(5+6y)=6 | | 20x-2=18x+6 | | -5=d/-29 | | 2g-14=2 | | 1-4n=-5n+1 | | m+-72=-43 | | [8x+4]=8 | | 16=r-25 | | -2+2m=m-5 | | 2.5x*x=250 | | 2(3x+4)=355 | | p/7=6 | | 10+x-3x=25 | | -5m+6=-8-7m | | 7j=-28 | | 2+3n-2=-9 | | (5/5x)-(4/5x)=(5x/5x) | | (x-5)+(x+35)+x+1.4=360 | | y-58=3 | | 1.5x+4.20=1.65x+3.15 | | x-5=x-2 | | (10x-25)/(2x-5 | | 8h-2+4h=2h+6 | | (1/x)-(4/5x)=1 | | 6x+2(-3x-4)=-1-7x | | (10x^2)-25-3x=0 |